Three new species of the genus Miridiba Reitter, 1902 (Scarabaeidae: Melolonthinae) from Vietnam along with a new country record - Pham, Phu Van; Keith, Denis; Pham, Nhi Thi; Cao, Nga Quynh Thi (Zootaxa, 2022)
Three new species of the genus Miridiba Reitter, 1902 from Vietnam are described and illustrated: Miridiba apicespinosa P.V. Pham & Keith, new species, M. ngoclinhensis P.V. Pham & Keith, new species, and M. quangnamensis P.V. Pham & Keith, new species. Miridiba bannaensis Gao & Fang, 2018 is reported for the first time from Vietnam. Additionally, an updated checklist and a key to all Vietnamese species are provided.